Reclaiming late-romantic music : singing devils and distant sounds - Franklin, Peter (Ernest Bloch lectures., 2014)
Why are some of the most beloved and frequently performed works of the late-romantic period-Mahler, Delius, Debussy, Sibelius, Puccini-regarded by many critics as perhaps not quite of the first rank? Why has modernist discourse continued to brand these works as overly sentimental and emotionally self-indulgent? Peter Franklin takes a close and even-handed look at how and why late-romantic symphonies and operas steered a complex course between modernism and mass culture in the period leading up to the Second World War. The style's continuing popularity and its domination of the film music idiom.